Network pharmacology associated anti-influenza mechanism research of Qingjie-Tuire Granule via STAT1/3 signaling pathway. Issue 3 (March 2023) - Wang, Yutao; Zhao, Xin; Xiao, Mengjie; Lin, Xiaoying; Chen, Qiaolian; Qin, Shengle; Ti, Huihui; Yang, Zifeng
Abstract: Qingjie-Tuire (QT) granule was approved for clinical use and its combination was reported to treat influenza infection. To explore its active component and mechanism, the components of QT granule were retrieved from UPLC-UC-Q-TOF/MS analysis. The genes corresponding to the targets were retrieved using GeneCards and TTD database. The herb–compound–target network was constructed by Cytoscape. The target protein–protein interaction network was built using STRING database. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of QT granule to IAV were performed for further study. The regulation to different signaling transduction events and cytokine/chemokine expression of QT granule was evaluated using Western blotting and real-time qPCR. Totally, 47 compounds were identified and effect of QT granule on cell STAT1/3 signaling pathways was confirmed by A549 cell model. The efficiency of QT granule on host cell contributes to its clinical application and mechanism research.